PERCEPTION ON OVERCOMING EMOTIONAL PROBLEMS THROUGH STRESS COPING STRATEGIES OF PROSPECTIVE TEACHERS DURING PANDEMIC SITUATION (International Journal of Food and Nutritional Sciences, 2021)
This study assessed the psychological distress, life satisfaction, and perceived stress of Ecuadorian teachers who adopted online learning in response to the COVID-19 pandemic. It also aimed to qualitatively report the coping strategies used to maintain their mental health and well-being.Although the teaching profession is stressful and despite the known impact of teachers' mental health on students during teaching, prospective teachers' mental health is neglected in training and selection. However, knowledge about teacher candidates' mental health during their training process and about their help-seeking behavior can contribute to improving their mental health. Therefore, this study aims at determining the mental state of teacher candidates and elucidating help-seeking behaviors that may be useful for overcoming mental problems.Student-teacher distress has the potential to impact on the individuals who are to become teachers, the profession and the education system. This review examines what is known of psychological distress among university students, teachers and student teachers, the demands associated with their practical experiences and the known impact of psychological distress.